AN ANALYSIS OF STUDENTS READING FINAL EXAMINATION BY USING ITEM ANALYSIS PROGRAM ON ELEVENTH GRADE OF SMA NEGERI 8 MEDAN - Dewi Manalu (English Education Department at FKIP Nommensen University, 2019)
The purpose of this study was to determine the quality of the reading final examination in SMA N8 Medan grade eleventh in terms of reliability, level difficulty, discrimination power and level of distractor. This research is qualitative-quantitative research. The subject of research are the grade XI of SMA N8 Medan. Data is analyzed by ANATES program version 4.0.9. The analysis shows that: (1) items of multiple choice question that can be said as valid are 14 items ( 56%), while the invalid items amounted to 11 items ( 44%). (2) Items mutiple choice question can said as reliable because it equal 0,90 so it can said reliable. (3) items of multiple choice questions that categorized easy are 3 items (12%), satisfactory category 7 ( 28%) difficult category 2 (8%) and the other calculate categorized very easy 3 items (12%) and very difficult 3 (12%). (4) items of multiple choice questions that categorized poor are 12 items (48%),average category are 2 items (8%), good items category 1 items (4%) and excellent items are 8 items (32%).